Control genetico de la resistencia del anublo de halo (Pseudomonas phaseolicola) en frijol y la busqueda por resistencia en variedades de Guatemala y otros paises - Figueroa, G (International Center for Tropical Agriculture, 1980)
Aspects on the distribution, etiology, symptomatology, genetic, cultural, and chemical control of the halo blight of beans, caused by Pseudomonas phaseolicola, are given. The results obtained in previous assessment and in trials on plant survival under field and greenhouse conditions of 6 bacterial pathogens of beans are discussed, along with an inoculation test of P. phaseolicola on selected climbing bean cv. Selected small black-seeded bean cv.G 3272, G 6036, G 6034, G 6339, G 790, G 984, G 2338, and G 5272 were resistant to the pathogen; selections of different colored large- seeded bean cv. had intermediate/susceptible reactions. (CIAT)